Oesterreicher im Burenkrieg 1899-1902; - De Jong, C. (Scientia Militaria - South African Journal of Military Studies, 2011)
Not only in South Africa and Great Britain there is an increased interest for the second Anglo-Boer War 1899-1902, but also in other countries for whom this war was far away and of limited importance. It is a matter apart to explain the remarkable interest in this colonial war fought long ago. Recently in Vienna the fifth Austrian doctoral thesis regarding this war since World War II has appeared. It is the work of Erwin A. Schmidl, a very thorough thesis, based on archival research in Austria, Britain and South Africa, visits to family of veterans in Austria and a tour of the museums and war memorials in South Africa.